How will we feed the hungry billions? Food for tomorrow's world - Hey, Nigel (New York, J. Messner, 1971)
Examines the methods used in the war against hunger such as development of high yield wheat, replacements for pesticides and herbicides, food preservation, irrigation of desert areas, and farming of the sea.
Keywords: Food supply -- Juvenile literature; Food supply